Genomic analysis of Campylobacter fetus subspecies: Identification of candidate virulence determinants and diagnostic assay targets - Moolhuijzen, Paula; Lew-Tabor, A.; Wlodek, B.; Agüero, F.; Comerci, D.; Ugalde, R.; Sanchez, D.; Appels, R.; Bellgard, M. (BioMed Central Ltd., 2009)
Background. Campylobacter fetus subspecies venerealis is the causative agent of bovine genital campylobacteriosis, asymptomatic in bulls the disease is spread to female cattle causing extensive reproductive loss. The microbiological and molecular differentiation of C. fetus subsp. venerealis from C. fetus subsp. fetus is extremely difficult. This study describes the analysis of the available C. fetus subsp. venerealis AZUL-94 strain genome (~75-80%) to identify elements exclusively found in C. fetus subsp. venerealis strains as potential diagnostic targets and the characterisation of subspecies virulence genes. Results. Eighty Kb of genomic sequence (22 contigs) was identified as unique to C. fetus subsp. venerealis AZUL-94 and consisted of type IV secretory pathway components, putative plasmid genes and hypothetical proteins. Of the 9 PCR assays developed to target C. fetus subsp. venerealis type IV secretion system genes, 4 of these were specific for C. fetus subsp. venerealis biovar venerealis and did not detect C. fetus subsp. venerealis biovar intermedius. Two assays were specific for C. fetus subsp. venerealis AZUL-94 strain, with a further single assay specific for the AZUL-94 strain and C. fetus subsp. venerealis biovar intermedius (and not the remaining C. fetus subsp. venerealis biovar venerealis strains tested). C. fetus subsp. fetus and C. fetus subsp. venerealis were found to share most common Campylobacter virulence factors such as SAP, chemotaxis, flagellar biosynthesis, 2-component systems and cytolethal distending toxin subunits (A, B, C). We did not however, identify in C. fetus the full complement of bacterial adherence candidates commonly found in other Campylobacter spp. Conclusion. The comparison of the available C. fetus subsp. venerealis genome sequence with the C. fetus subsp. fetus genome identified 80 kb of unique C. fetus subsp. venerealis AZUL94 sequence, with subsequent PCR confirmation demonstrating inconsistent amplification of these targets in all other C. fetus subsp. venerealis strains and biovars tested. The assays developed here highlight the complexity of targeting strain specific virulence genes for field studies for the molecular identification and epidemiology of C. fetus. © 2009 Moolhuijzen et al; licensee BioMed Central Ltd.